The Role of Padepokan Ciliwung Condet in The Development of Betawi Cultural Tourism Ciliwung Condet - Suyono, Prama Hardika; Nugraha, Rizki Nurul (Westscience Press, 2024)
This research aims to examine the role of Padepokan Ciliwung Condet in developing Betawi cultural tourism in the Ciliwung Condet area. Betawi cultural tourism has great potential as a tourism attraction that can make a positive contribution to the local economy and preserve regional culture. Padepokan Ciliwung Condet, as a center for Betawi arts and cultural activities, is the main subject of this research. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, direct observation and documentation studies. The research results show that Padepokan Ciliwung Condet has a significant role in developing Betawi cultural tourism. The Padepokan functions as a place for training in traditional Betawi arts, art exhibitions and a cultural information center. In the context of tourism development, Padepokan Ciliwung Condet plays a role in creating an authentic and memorable tourism experience for visitors. Its existence also contributes to the preservation of Betawi arts and culture, as well as promoting local community participation in the tourism industry. This research provides recommendations for increasing the role of Padepokan Ciliwung Condet in the development of Betawi cultural tourism, including more effective marketing strategies, improving infrastructure, and closer cooperation between related parties. Thus, it is hoped that the development of Betawi cultural tourism in Ciliwung Condet can have a sustainable positive impact on the local community and preserve the regional cultural heritage.